Lipopolysaccharides from Bacteroides fragilis are mitogenic for spleen cells from endotoxin responder and nonresponder mice. - Joiner, K A (1982)
The lipopolysaccharides (LPS) from Bacteroides fragilis are structurally atypical and give weak responses in most tests of endotoxic activity, but the mitogenic activity of LPS from B. fragilis has not been tested. We prepared LPS from B. fragilis 23745 by three methods and compared their mitogenic activity for murine spleen cells with that of LPS from Escherichia coli K235 prepared by similar techniques. LPS extracted from B. fragilis with hot phenol-water, with butanol-water, or by detergent separation from the outer membrane were mitogenic for spleen cells from C57BL/10ScN, C57BL/10ScCR, and C3H/HeJ mice. The outer membrane, the outer membrane protein-polysaccharide complex, and the capsular polysaccharide from B. fragilis were also mitogenic for spleen cells from the same murine strains. LPS extracted from E. coli K235 with hot phenol-water, butanol-water, or sodium deoxycholate were mitogenic for C57BL/10ScN spleen cells, but only the LPS extracted with butanol and deoxycholate were stimulatory for spleen cells from C57BL/10ScCR and C3H/HeJ mice. Two types of LPS varying in the 2-keto-3-deoxyoctonate-to-carbohydrate ratio were isolated from E. coli K235 with sodium deoxycholate; both endotoxins contained protein which was typical of lipid A or endotoxin protein. These results indicate that the LPS from B. fragilis is a potent mitogen for spleen cells from endotoxin responder and endotoxin nonresponder mice.